Analysis of the Application of the Maslahah Concept in DSN MUI Fatwa in the Sector of Sharia Economics and Finance - Mujahidin Mujahidin (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
The purpose of this study is to analyze the Application of the Maslahah Concept in DSN MUI Fatwa in the Sector of Sharia Economics and Finance. The concept of maslahah, or public interest, is a fundamental principle in Islamic jurisprudence that is also applied in the fatwas issued by the Indonesian Council of Ulama's (MUI) Shariah Supervisory Board (DSN). The application of the maslahah concept in DSN MUI's fatwas is crucial to ensure that the decisions made are in the best interest of the Muslim community and promote the well-being of society. Research method is Library research refers to the process of searching for and analyzing information in a library setting. This can involve searching for books, articles, and other sources of information related to a specific topic or research question. Result of the research maslahah concept is applied in DSN MUI's fatwas is by considering the broader societal impacts of a particular issue or problem. For instance, in the context of Islamic finance and banking, DSN MUI has issued fatwas that aim to promote financial stability, economic growth, and social justice. This is achieved by ensuring that Islamic financial institutions adhere to Shariah principles and avoid practices that are harmful to society or the environment. Moreover, the maslahah concept is also used to address new issues and challenges that arise in modern society. For example, DSN MUI has issued fatwas on digital currencies and e-commerce that take into account the unique characteristics of these new technologies and how they can be used to promote the well-being of society while adhering to Islamic principles.. Keywords: DSN MUI; Mashlahah; Sharia Economic; Finance; Fatwa.